2012
DOI: 10.5402/2012/424105
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Biogas Conversion Technology for Economic Development: A Case Study in Kilimanjaro Region

Abstract: In Tanzania the overall performance of the country's social and economic development requires the minimization of the existing energy challenges. Currently, about 80% of Tanzanians live in rural areas, and 90% percent of the populations have no access to grid electricity but rely on fuel wood and charcoal, causing annual deforestation rates of about 500,000 hectares. This problem can be minimised, especially where there is potential, like Kilimanjaro region. However, the level of development of biogas in the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…It has been reported that up to 0.5 gigam 3 of biogas could be produced daily in Kilimanjaro region of Tanzania. This exceeds by far the 0.72 million m 3 required for cooking in the region while 3.0 MWh energy required for small economic activity in the region is about 0.15 of the total energy that can be generated from agro waste materials ( Mkiramweni, 2012 ). Also, Ahmmad and Haque (2014) has estimated the potentiality to generate electricity as 207.288, 873.034 and 2878.134 MW/day in 2020, 2025 and 2050 using municipal solid waste in Dhaka City of Bangladesh.…”
Section: Sustaining Covid-19 Era Lockdown Environment Through Renewable Energy Resourcesmentioning
confidence: 93%
“…It has been reported that up to 0.5 gigam 3 of biogas could be produced daily in Kilimanjaro region of Tanzania. This exceeds by far the 0.72 million m 3 required for cooking in the region while 3.0 MWh energy required for small economic activity in the region is about 0.15 of the total energy that can be generated from agro waste materials ( Mkiramweni, 2012 ). Also, Ahmmad and Haque (2014) has estimated the potentiality to generate electricity as 207.288, 873.034 and 2878.134 MW/day in 2020, 2025 and 2050 using municipal solid waste in Dhaka City of Bangladesh.…”
Section: Sustaining Covid-19 Era Lockdown Environment Through Renewable Energy Resourcesmentioning
confidence: 93%
“…Energy challenges in Tanzania affect seriously the performance of the country's social and economic sector (Felix and Gheewala, 2011). Poor income, poor health, and education indicators can greatly be improved with adaptation of clean and modern energy (Mkiramweni, 2012). It is estimated that 80% of Tanzanians depend on biomass as a source of energy by burning firewood and charcoal.…”
Section: Social Economic Benefitsmentioning
confidence: 99%
“…It is estimated that 80% of Tanzanians depend on biomass as a source of energy by burning firewood and charcoal. Application of algae as a source of biofuel will potentially reduce the burden on the forest resources as well as consequences of air pollution which can lead to complications of breathing, chronic respiratory diseases and stinging eyes due to indoor air pollution that comes from burning charcoal and firewood inside homes (Mkiramweni, 2012). Nutrients from wastewater through utilization of microalgae for animal feed will improve individual's incomes since algal products will supplement the conventional source of food which is always expensive.…”
Section: Social Economic Benefitsmentioning
confidence: 99%
“…About 23% of the people in the country use electricity for lighting this cannot facilitate improved student performance. Specifically, the sources of energy being used by the majority of Tanzanians are either very ineffective and/or inefficient for realizing the socioeconomic development [15]. It would also reduce environmental pollution such as air pollution caused by burning of fossil fuels and improve public health, reduce premature mortality due to pollution and save associated health costs that amount to several 100 billion dollars annually only in the United States [16].…”
Section: Introductionmentioning
confidence: 99%
“…Contour plot graph of optimizationThis result in maximum conditions was at mixing ratio of 0.65 and retention time of 37 days. The final equation was defined a repeat of equation(15):Let Cumulative biogas yield in Liters = Y L, Mixing ratio = X 1 , HRT = X 2…”
mentioning
confidence: 99%